Desempenho de escolares com transtorno do déficit de atenção com hiperatividade em habilidades metalinguísticas, leitura e compreensão leitora - Uvo, Mariana Ferraz Conti; Germano, Giseli Donadon; Capellini, Simone Aparecida (ABRAMO Associação Brasileira de Motricidade Orofacial, 2017)
ABSTRACTPurpose:to characterize and compare the performance of students with Attention Deficit Hyperactivity Disorder in metalinguistic skills, reading and reading comprehension in students with good academic performance.Methods:30 participants from primary schools, of both genders, aged from 8 to 12 years and 11 months, divided into two groups: Group I consisted of 15 students diagnosed with Attention Deficit Hyperactivity Disorder and Group II composed of 15 students with good academic performance. The students were matched byage, grade level and gender. The students were submitted to Metalinguistic Skills Tests, Reading Protocol and Reading Comprehension Tests.Results:differences were found between Group I and Group II for skills regarding initial and final phonemic identification, syllable and phonemes subtraction and addition, as well as phonemic segmentation. The performance of Group I was also inferior than that of Group II, in Reading protocol and repetition of non-words. There was no statistically significant difference between the groups in reading comprehension performance.Conclusion:students with Attention Deficit Hyperactivity Disorder presented inferior performance in relation to reading protocol and in more complex metalinguistic skills, which required retention, analysis and information retrieval, when compared to the control group. In regard to reading comprehension, both groups presented lower performance, with similar results.

RESUMOObjetivo:caracterizar e comparar o desempenho de escolares com Transtorno do Déficit de Atenção com Hiperatividade em habilidades metalinguísticas, leitura e compreensão leitora, com escolares de bom desempenho acadêmico.Métodos:participaram deste estudo 30 escolares do Ensino Fundamental I, de ambos os gêneros, na faixa etária de 8 anos a 12 anos e 11 meses de idade, divididos em dois grupos: Grupo I, composto por 15 escolares com diagnóstico de Transtorno do Déficit de Atenção com Hiperatividade; Grupo II, composto por 15 escolares com bom desempenho acadêmico. Os escolares foram pareados em relação à idade, à escolaridade e ao gênero e foram submetidos à aplicação das provas de habilidades metalinguísticas, de leitura e de compreensão de leitura.Resultados:foi possível verificar desempenho inferior do GI em habilidades de identificação de fonema inicial e final, subtração e adição de sílabas e de fonemas, bem como de segmentação de fonemas. O desempenho do GI também foi inferior ao do GII em provas de leitura e de repetição de não palavras. Não houve diferença estatisticamente significante entre o desempenho dos grupos em compreensão leitora.Conclusão:os escolares com Transtorno do Déficit de Atenção com Hiperatividade em comparação com grupo controle apresentaram desempenho inferior na decodificação leitora e nas tarefas metalinguísticas consideradas mais complexas, as quais exigem retenção, análise e recuperação de informação. Na compreensão de leitura ambos os grupos apresentaram classificação de desempenho inferior com resultados semelhantes.
Performance of students with attention deficit hyperactivity disorder in metalinguistic skills, reading and reading comprehension
Keywords: Learning; Reading; Evaluation; Education; Attention Deficit Hyperactivity Disorder; Aprendizagem; Leitura; Avaliação; Educação; Transtorno do Déficit de Atenção com Hiperatividade